2004
DOI: 10.1002/chin.200409202
|View full text |Cite
|
Sign up to set email alerts
|

Endcaps for Stabilizing Short DNA Duplexes

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In addition, we prepared the terthiophene spacer 2 , which provided an opportunity to study and compare an exceptionally hydrophobic endcap. Several research groups had reported that hydrophobic, aromatic molecules such as naphthalene diimides 32–34 (3,12,17), N , N -dimethylstilbene dicarboxamide (8), trimethoxystilbenes(18) and stilbene ether (9) stabilized DNA duplexes through stacking interactions with the DNA bases. We expected that endcap 2, with a terthiophene core, would also have significant stacking interactions with the base pairs in a DNA duplex.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we prepared the terthiophene spacer 2 , which provided an opportunity to study and compare an exceptionally hydrophobic endcap. Several research groups had reported that hydrophobic, aromatic molecules such as naphthalene diimides 32–34 (3,12,17), N , N -dimethylstilbene dicarboxamide (8), trimethoxystilbenes(18) and stilbene ether (9) stabilized DNA duplexes through stacking interactions with the DNA bases. We expected that endcap 2, with a terthiophene core, would also have significant stacking interactions with the base pairs in a DNA duplex.…”
Section: Resultsmentioning
confidence: 99%